The ENL moiety of the childhood leukemia-associated MLL-ENL oncoprotein recruits human Polycomb 3 - Garcia-Cuellar, Maria-Paz; Zilles, Olaf; Schreiner, Silke; Birke, Marco; Winkler, Thomas; Slany, Robert (Oncogene, 2001)
The translocation t(11;19) is frequently found in acute leukemia in infants. This event truncates the protooncogene MLL and fuses the 5′ end of MLL in frame with the ENL gene. ENL contributes a crucial protein-protein interaction domain to the resulting oncoprotein MLL-ENL. Here we show by yeast two-hybrid assays, GST-pull-down experiments and in a far western blot analysis that this domain is necessary and sufficient to recruit a novel member of the human Polycomb protein family (hPc3). hPc3 RNA was detected throughout the human hematopoietic system. Similar to other Polycomb proteins hPc3 acts as a transcriptional repressor. The ENL-hPc3 interaction was verified by mutual coprecipitation of the proteins from cell extracts. ENL and hPc3 tagged with fluorescent proteins co-localized in living cells in a nuclear dot pattern. An internal region of hPc3 was responsible for binding to ENL. Finally, hPc3 binds to the C-terminus of AF9, another common MLL fusion partner. The recruitment of a repressive function by ENL opens up a new insight into a possible mechanism of leukemogenesis by the fusion protein MLL-ENL.
UnivIS-Import:2015-03-09:Pub.2001.nat.dbio.geneti.theenl
Keywords: ENL; Leukemia; MLL; Polycomb; Translocation